Reviving Ottoman Bird Palaces and Retro Approach with Additive Manufacting Method - Çalışkan, Cemal İrfan (Elsevier, 2019)
In recent years, three-dimensional printing technology has begun to be used as an alternative production technique as well as classical methods with technological developments. The Additive manufacturing (AM) production technique, which increasing use in recent years allows rapid prototyping as well as the production of complex designs. With this technology, we wanted to take a step to revitalize the lost cultural heritage of the bird palaces that can be expressed as miniature architectural items of the ancient Turkish culture.
Keywords: Birdhouse; Birdpalaces; 3d Printing; Additive Manufacturing; Architecture; Industrial Design; Design; Ottoman Architecture